Automated locomotor activity monitoring as a quality control assay for mass‐reared tephritid flies. Issue 2 (11th July 2013) - Dominiak, Bernard C; Fanson, Benjamin G; Collins, Samuel R; Taylor, Phillip W
Abstract BACKGROUND The Sterile Insect Technique (SIT) requires vast numbers of consistently high quality insects to be produced over long periods. Quality control (QC) procedures are critical to effective SIT, both providing quality assurance and warning of operational deficiencies. We here present a potential new QC assay for mass rearing of Queensland fruit flies (Bactrocera tryoni Froggatt) for SIT; locomotor activity monitoring. We investigated whether automated locomotor activity monitors (LAMs) that simply detect how often a fly passes an infrared sensor in a glass tube might provide similar insights but with much greater economy. RESULTS Activity levels were generally lower for females than for males, and declined over five days in the monitor for both sexes. Female activity levels were not affected by irradiation, but males irradiated at 60 or 70 Gy had reduced activity levels compared with unirradiated controls. We also found some evidence that mild heat shock of pupae results in adults with reduced activity. CONCLUSION LAM offers a convenient, effective and economical assay to probe such changes. © 2013 Society of Chemical Industry